Gregory of Nyssa : Contra Eunomium III : an English translation with commentary and supporting studies : proceedings of the 12th International Colloquium On Gregory Of Nyssa (Leuven, 14-17 September 2010) - Leemans, Johan, 1965-; Cassin, Matthieu. (Vigiliae Christianae, Supplements, 2014)
Gregory of Nyssa's Contra Eunomium , one of the major books on trinitarian theology of the 4th century, documents the exchange between Eunomius and the Cappadocian Father in the last episode of the so-called \'Arian Crisis\'. The present volume is devoted to the third and last book of Contra Eunomium . It offers a fresh English translation with a running commentary in the form of ten studies by first-rank specialists. Seventeen shorter papers enlighten various aspects of Contra Eunomium and other writings of the same author. The contributions will be of interest for scholars of historical and systematical theology, philosophy, spirituality, rhetoric and the history of the Early Church.